A Short Of Review On Pancreatic β- Cell Function In Diabetes Mellitus Patients - Mahapatra, Hariballav; Sahu, Jaydeep Kumar; Pandey, Akanksha; Javed, Danish; Ramya.P, Ramya.P; Tripathi, Dinesh (Journal of Neonatal Surgery, 2025)
According to a study, IR & β-cell DF are involved in the onset and advancement of T2D. In addition to the harmful consequences of IR, IFM & OS have become significant characteristics that delineate β-cell DF. Key inflammatory markers, including CRP, TNF-α and IL-1β linked to β-cell DF in preclinical models. These effects demonstrate a PAT association between an aberrant IFM response and the production of OS in the advancement of T2D. Therefore, in this review we have discussed about the normal function and pathological aspect of β- cell.